Visible light-driven NH2Cl activation by g-C3N4 photocatalysis producing reactive nitrogen species to degrade bisphenol A. (15th May 2023) - Cheng, Xin; Cheng, Zihang; Jing, Binghua; Ao, Zhimin; Shang, Chii; Ling, Li
Highlights: A visible light-driven g-C3 N4 photocatalytic NH2 Cl activation process is developed to produces RNS for BPA degradation. e CB − and O 2 − induce N–Cl bond cleavage to produce NH2, NH2 OO, NO and NO2 . h VB + induces N–Cl bond cleavage to produce NHCl and NHClOO. The process converts 73.5% of decomposed NH2 Cl to Nitrogen-containing gas. The process is less affected by aqueous components than UVC/NH2 Cl process. Abstract: The photolysis of monochloramine (NH2 Cl), a widely used disinfectant, under UVC irradiation produces different radicals for the micropollutant degradation. For the first time, this study demonstrates the degradation of bisphenol A (BPA) via the NH2 Cl activation by graphitic carbon nitride (g-C3 N4 ) photocatalysis using visible light-LEDs at 420 nm, termed as the Vis420 /g-C3 N4 /NH2 Cl process. The process produces NH2, NH2 OO, NO and NO2 via the e CB − - and O 2 − -induced activation pathways and NHCl and NHClOO via the h VB + -induced activation pathway. The produced reactive nitrogen species (RNS) enhanced 100% of the BPA degradation compared with the Vis420 /g-C3 N4 . Density functional theory calculations confirmed the proposed NH2 Cl activation pathways and further demonstrated that e CB − / O 2 − and h VB + induced the cleavage of N–Cl and N–H bonds in NH2 Cl, respectively. The process converted 73.5% of the decomposed NH2 Cl to nitrogen-containing gas, compared with that of approximately 20% in the UVC/NH2 Cl process, leaving much less ammonia, nitrite and nitrate in water. Among different operating conditions and water matrices tested, of particular significance is natural organic matter of 5 mgDOC/L only reduced 13.1% of the BPA degradation compared against that of at least 46% reduction in the UVC/NH2 Cl process. Only 0.017–0.161 µg/L of disinfection byproducts were produced, two orders of magnitudes lower than that in the UVC/chlorine and UVC/NH2 Cl processes. The combined use of visible light-LEDs, g-C3 N4 and NH2 Cl significantly improves the micropollutant degradation and reduces the energy consumption and byproduct formation of the NH2 Cl-based AOP. Graphical abstract: Image, graphical abstract